METHODOLOGY FOR DESIGNING NEW MODULES BASED ON GAMIFICATION IN STEAM EDUCATION. (Universal International Scientific Journal, 2026)
This study examines the theoretical and practical foundations of designing educational modules in the STEAM (Science, Technology, Engineering, Arts, Mathematics) education field based on the principles of gamification. The article proposes a methodology for moving from traditional educational methods to interactive, game-enriched modules. It also analyzes the impact of gamification on students' cognitive activity and its strategic importance in training a new generation of personnel.
Keywords: STEAM education, gamification, learning module, design methodology, cognitive motivation, 21st century skills, interactive environment.